Oxygen‐derived free radicals: Production, biological importance, bioimaging, and analytical detection with responsive luminescent nanoprobes. Issue 5 (22nd June 2021) - Liu, Jianping; Wu, Miaomiao; Zhang, Run; Xu, Zhi Ping
Abstract: Oxygen‐derived free radicals (ODFRs) are partially reduced oxygen reactive intermediates in living organisms during various biological processes, such as mitochondrial respirations, enzyme‐catalyzed oxidations, and radiolysis. Of various ODFRs being identified, superoxide anion (O2 – ) and hydroxyl (OH) radicals are extensively investigated. Due to their high reactivity, these radicals can oxidize many biomolecules, including nucleic acids, proteins, lipids, and carbohydrates, which would damage some key cellular components. Under oxidative stress, elevated oxygen radical levels are closely associated with various diseases, such as neurodegenerative diseases, cardiovascular diseases, rheumatoid arthritis, and cancers. In this context, a number of responsive nanoprobes have been developed for luminescent detection of ODFRs in living organisms. In this review, we briefly introduce the production of ODFRs and their biological importance for various diseases. We then extensively summarize responsive nanoprobes for detection and bioimaging of these two oxygen radicals, O2 – and OH, which are designed and developed based on their specific oxidation mechanisms in the recent decade. Challenges and some future research directions are also proposed as the conclusion. Abstract : This review briefly summarizes the oxygen‐derived free radicals' production, biological properties, and their roles in the development of various diseases, and then intensively reviews responsive nanoprobes for two major oxygen radicals, that is, superoxide anion and hydroxyl radicals. The comparison of these nanoprobes and future perspectives in oxygen radical studies are provided as the conclusion.